Evaluating the Sub-Lethal Effects of Malathion on Biochemical Parameters of Freshwater Fish Labeo rohita (Hamilton) - M. Venkatewara Rao; K. Thirupathi; Venkaiah Yanamala (Research Perspective on Biological Science Vol. 4, 2025)
Malathion is a non-systemic, wide-spectrum organophosphate insecticide. Organophosphates are widely used throughout the world as an important group of pesticides, due to their insecticidal property, less toxicity, less persistence and rapid biodegradability in the environment. The present investigation was undertaken to study the toxic effect of Malathion on biochemical parameters of the freshwater fish Labeo rohita (Hamilton). The freshwater fish Labeo rohita were collected from local freshwater culture ponds by netting with the help of local fishermen located within the study region. The fish were exposed to sub-lethal concentrations of the insecticide Malathion and the variations were observed on different parameters, i.e. proteins, carbohydrates and ninhydrine positive substances (FAA) at different time intervals, i.e. 24, 48, 72 and 96 hrs of Malathion exposure from different tissues of fish Labeo rohita, i.e. gill, liver, intestine, muscle and brain. Statistical analysis was performed by ANOVA to compare the results between the tissue components. The results revealed that biochemical constituents, i.e. proteins, carbohydrates and ninhydrine-positive substances, were decreased in all the tissues of L. rohita. The toxic nature of insecticide Malathion was found to be more after 48 hours of exposure, as the highest % of decrease was found in biochemical constituents of all the tissues. This study concluded that the sublethal effects of Malathion on biochemical parameters of fresh freshwater fish L. Rohita. Therefore, the usage of pesticides should be restricted to a minimal concentration to have a healthy ecosystem.